(untitled) (Indonesian Minority Justice Review, 2024)
This paper examines the legal challenges faced by Indonesia’s LGBTQ+ community, focusing on the legal struggles for recognition, protection, and rights within a predominantly conservative and religious society. While same-sex relationships are not explicitly criminalized under Indonesian law, LGBTQ+ individuals often face harassment, discrimination, and violence, exacerbated by societal stigma and political opposition. The study investigates the legal landscape for LGBTQ+ rights, analyzing the lack of protective laws, the impact of regional by-laws that criminalize homosexual acts, and the social and political context that complicates legal protections. Through case studies, interviews with LGBTQ+ activists, and legal experts, the paper highlights the ways in which LGBTQ+ individuals are excluded from legal protections such as marriage, inheritance, and employment rights. The findings show that despite some civil society efforts, legal reform has been slow, and LGBTQ+ individuals remain marginalized in both legal and social contexts. The paper concludes by calling for comprehensive legal reforms, including the decriminalization of same-sex relationships, anti-discrimination laws, and a broader cultural shift towards acceptance, in order to defend the rights and dignity of Indonesia’s LGBTQ+ community.